Hull Number Effect in Ship Using Conveyor on Ocean Waste Collection - Sugianto, Erik; Winarno, Arif; Indriyani, Ratna; Horng Chen, Jeng (Department of Naval Architecture - Diponegoro University, 2021)
The increase in ocean waste continues to grow from year to year, especially plastic and solid waste. Various ocean waste collection ships using conveyors exist, both in the form of designs and already in operation, but there has been no research on how many hulls are suitable for ocean waste collectors. This study aims to choose between the three-ship models, namely monohull type U, catamaran type inner flat hull, and trimaran type symmetrical. Assessment is based on ship resistance which relates to fuel consumption and flow distribution relates to ocean waste collection. This research uses Computational Fluid Dynamics (CFD) method which produces resistance, fluid flow velocity contours, and fluid flow patterns. Numerical simulation is based on Reynolds Averaged Navier Stokes (RANS). The turbulent model uses the standard k-epsilon equation. Then the volume of fluid sub-models used is open channel flow. The number of eulerian phases is two. Moreover, Â formulation of the volume fraction parameters used is an implicit body force. The results show that monohull type U is better than others in easiest to bring ocean waste closer to the conveyor and smallest resistance force. Then symmetric trimaran is faster than others in making ocean waste flow to the conveyor.